Morphological expression of angiogenesis in the mammalian ovary as seen by SEM of corrosion casts - Macchiarelli, Guido; Nottola, Stefania A.; Palmerini, Maria Grazia; Bianchi, Serena; Maione, Marta; Lorenzo, Caterina; Stifano, Giuseppe; Di Marco, Elena; Correr, Silvia (Italian Journal of Anatomy and Embryology, 2010)
In the mammalian ovary, follicular and corpus luteum cycle is associated with intensive microvascular remodelling. The complex angiogenic dynamics are finely tuned by numerous regulatory factors acting as activators (upregulators) or inhibitors (downregulators) of angiogenesis. Alterations of such a tight modulation are involved in several pathologies, including infertility, polycystic ovarian syndrome, ovarian hyperstimulation syndrome and ovarian cancer. We have demonstrated in several experimental models that ovarian function is critically and specifically dependent on angiogenesis for follicular development, ovulation, and corpus luteum growth. The aim of this review is to summarize the results we have obtained on the morphodynamic remodelling of ovarian microvascularization, in polyovulatory (rat, rabbit and pig) and monovulatory species (cow), using scanning electron microscopy of vascular corrosion casts. The knowledge of the morphological expression of the up and downregulation of angiogenesis occurring in mono and polyovulatory animals might provide useful information to preserve fertility and to increase of the effectiveness of reproductive management in species of domestic interest.